2010
DOI: 10.1039/c0jm02602f
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic ferrite/perovskite oxide core/shell nanostructures

Abstract: A general combined hydrothermal and annealing process for the fabrication of ferrite/perovskite oxide core/shell nanostructures was introduced. The coating of a perovskite oxide (ABO 3 ) layer on spherical ferrite particles was performed in two steps. A dense and smooth amorphous layer containing B-site ions of the perovskite oxide was coated first via a controlled hydrolysis and aging process. During hydrothermal treatment and subsequent annealing process, the A-site ions were incorporated in situ into the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 32 publications
(27 reference statements)
0
45
0
Order By: Relevance
“…Tatarenko et al [131] reported the converse ME effect over the [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] GHz range in bilayers of single crystal ZnY and polycrystalline PZT or single crystal PMN-PT. The resonator was tuned by 120 MHz with E = 12 kV/cm, and corresponding ME coupling strength A was about 10 MHz cm/kOe.…”
Section: Resonatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tatarenko et al [131] reported the converse ME effect over the [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] GHz range in bilayers of single crystal ZnY and polycrystalline PZT or single crystal PMN-PT. The resonator was tuned by 120 MHz with E = 12 kV/cm, and corresponding ME coupling strength A was about 10 MHz cm/kOe.…”
Section: Resonatorsmentioning
confidence: 99%
“…A modified precipitation method involving a controlled annealing, quenching, and aging cycle [16] has been employed to obtain good dispersion of ferrite (NiFe 1.9 Mn 0.1 O 4 ) particles in the matrix (PZT) phase. Core/shell (ferrite/piezoceramic) structured composites have been synthesized to avoid the contact of the conductive ferrite particles during sintering [17]. Unlike the other cases, Islam et al [18] reported a PZT core/NiFe 2 O 4 shell ME composite (Figure 3c).…”
Section: Bulk Me Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanostructures of core-shell particles, pillars in a host matrix, coaxial tubes and wires have been studied in recent years. [26][27][28][29][30][31][32][33][34][35] The strength of ME coupling in these systems was studied by several techniques including piezo force microscopy and magnetic force microscopy. [35][36][37] Theories predict strong ME coupling in these systems.…”
Section: -6mentioning
confidence: 99%
“…For this reason, an increase in the area of the interface through which magnetostriction or electrostriction propagates to other phases is considered to be effective for increasing the ME effect. 9,10,12,13 Moreover, the formation of an anisotropic interface between magnetostrictive and electrostrictive materials is essential for increasing the ME effect.…”
mentioning
confidence: 99%